Dental students' perceptions of learning space: A focus group study - Lau, May Nak; Sivarajan, Saritha; Mohd Yusof, Zamros Yuzadi (Penerbit Universiti Sains Malaysia, 2020)
Optimal learning space enhances teaching and learning experience and may differ from one discipline to another. This research aimed to explore the opinions on learning spaces for teaching and learning orthodontic course among recent dental graduates. Focus group discussions (FGD) were conducted in 2018 with two groups of recent graduates (eight participants per group) based on their orthodontic examination results (high and low grades). They were asked to give their opinions on the learning space provided for orthodontic lectures, tutorials, clinics, self-study and networking. Discussions during the FGD were audio and video recorded. Data were transcribed and thematically analysed using the NVivo version 12 software. For lectures, the graduates preferred a conventional lecture hall layout with an individual power outlet and a desk large enough for a laptop. For tutorials, the graduates with higher grades preferred e-tutorials while the graduates with lower grades preferred the conventional tutorials. For clinical teaching, the graduates perceived the laboratory’s operating hours as limited and suggested a 24-h access card. The graduates preferred live-streaming sessions instead of on-site teachings for combined clinics. They also felt that they do not have time for self-study and networking during their time in the campus. The findings of the study showed that learning space preferences of undergraduate dental students for lecture, tutorial, clinic, self-study and networking were more focused towards their learning activities, which were different from the current concept of learning space. Future planning of learning space should consider students’ preferences in order to fulfil their learning goals. © 2020 Penerbit Universiti Sains Malaysia